Imaging urban complexity: A Humanities approach in tropes, media, and genres - Korsten, Frans-Willem; Albright, Anthony T. (London Routledge, 2025)
Imagining Urban Complexity introduces passionate and critical perspectives on the link between the humanities and urban studies. It emphasizes tropes, media, and genres as cultural techniques that shape complexity in urban environments by distributing affordances, modes of sensing, and modes of sense-making.